Mia Mayhem and the Cat Burglar - West, Kara,Hernandez, Leeza (Little Simon, 2022)
Intro – Title Page – Chapter 1: A Special Invitation – Chapter 2: Pets at the PITS? – Chapter 3: The PITS is a Zoo! – Chapter 4: The Hidden Vault – Chapter 5: The Treasure Hunt – Chapter 6: The Cat Standoff – Chapter 7: Pets on the Run – Chapter 8: Chaos Brings Chaos – Chapter 9: Who's to Blame? – Chapter 10: The Super Pet Secret – About the Author and Illustrator – Copyright. Mia brings her cat, Chaos Macarooney, to PITS Day, and must keep the peace between Chaos and Hugo Fast's cat, Mr. Whiskers, before total chaos breaks out
Description based on publisher supplied metadata and other sources
Keywords: Cats-Fiction; African Americans-Fiction; Cats; Ability; Superheroes; African Americans; Electronic books